A novel near-infrared nanomaterial with high quantum efficiency and its applications in real time in vivo imaging. (22nd March 2018) - Cui, X X; Fan, Q; Shi, S J; Wen, W H; Chen, D F; Guo, H T; Xu, Y T; Gao, F; Nie, R Z; Ford, Harold D; Tang, Gordon H; Hou, C Q; et al.
Abstract: Fluorescence imaging signal is severely limited by the quantum efficiency and emission wavelength. To overcome these challenges, novel NIR-emitting K5 NdLi2 F10 nanoparticles under NIR excitation was introduced as fluorescence imaging probe for the first time. The photostability of K5 NdLi2 F10 nanoparticles in the water, phosphate buffer saline, fetal bovine serum and living mice was investigated. The fluorescence signal was detected with depths of 3.5 and 2.0 cm in phantom and pork tissue, respectively. Fluorescence spectrum with a significant signal-to-background ratio of 10:1 was captured in living mice. Moreover, clear NIR images were virtualized for the living mice after intravenous injection. The imaging ability of nanoparticles in tumor-beard mice were evaluated, the enrichment of K5 NdLi2 F10 nanoparticles in tumor site due to the enhanced permeability and retention effect was confirmed. The systematic studies of toxicity, bio-distribution and in-vivo dynamic imaging suggest that these materials give high biocompatibility and low toxicity. These NIR-emitting nanoparticles with high quantum efficiency, high penetration and low toxicity might facilitate tumor identification in deep tissues more sensitively.